2014
DOI: 10.1007/s00520-014-2329-6
|View full text |Cite
|
Sign up to set email alerts
|

Caregivers’ attachment patterns and their interactions with cancer patients’ patterns

Abstract: The attachment style of a caregiver can influence how they respond to a patient's needs. Studies have found that attachment anxiety or avoidance is more likely to interfere with effective and sensitive caregiving.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
21
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 62 publications
3
21
0
Order By: Relevance
“…Findings from the reviewed studies revealed a statistically significant association between higher levels of insecure attachment (avoidant attachment and anxious attachment) and higher levels of depressive symptoms, anxiety, and lower levels of social support. This is consistent with prior research investigating attachment and psychological well-being in mixed-stage cancer populations [28,29] and attachment and depression in non-cancer populations [66][67][68][69][70][71][72].…”
Section: Discussionsupporting
confidence: 91%
“…Findings from the reviewed studies revealed a statistically significant association between higher levels of insecure attachment (avoidant attachment and anxious attachment) and higher levels of depressive symptoms, anxiety, and lower levels of social support. This is consistent with prior research investigating attachment and psychological well-being in mixed-stage cancer populations [28,29] and attachment and depression in non-cancer populations [66][67][68][69][70][71][72].…”
Section: Discussionsupporting
confidence: 91%
“…This is consistent with previous findings(Manne, Badr, Zaider, Nelson, & Kissane, 2010;Regan et al, 2014;Tsilika, Parpa, Zygogianni, Kouloulias, & Mystakidou, 2015). Taken all together, complex interrelations suggest first of all that providing support for another person in burdensome disease situations is strongly related with personal distress on an individual level.…”
supporting
confidence: 92%
“…In particular, the quality of the relationship between the carer and care‐receiver appears to be central to the expression of positive experiences (Li & Loke, ). Factors such as frequency and intensity of interaction, relationship satisfaction, motivation to care, quality of communication, supportiveness and collaborative coping were also cited as influential variables (Chen et al., ; Elliott (nee Murray), Scott, Monsour, & Nuwayhid, ; Gustavsson‐Lilius et al., ; Kim, Carver, Deci, & Kasser, ; Pitceathly & Maguire, ; Tsilika, Parpa, Zygogianni, Kouloulias, & Mystakidou, ; Valeberg & Grov, ; Zwahlen et al., ). Hence, contextual factors that precede the caring role are an important component in the expression of positive aspects of caring.…”
Section: Resultsmentioning
confidence: 99%